2007
DOI: 10.1111/j.1365-3156.2007.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Dramatically decreased therapeutic efficacy of chloroquine and sulfadoxine‐pyrimethamine, but not mefloquine, in southern Benin

Abstract: Summaryobjective To evaluate the in vivo therapeutic efficacy of chloroquine (CQ), sulfadoxinepyrimethamine (SP) and mefloquine (MQ) in children presenting with uncomplicated malaria in Benin.methods Drug efficacy was tested according to the WHO in vivo 28-day protocol. For failures that occurred after 7 days of follow-up, paired pre-and post-treatment blood samples were genotyped at msp1 and msp2 loci to distinguish new infections and recrudescent strains. Children enrolled were randomly assigned to a therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 17 publications
1
29
1
Order By: Relevance
“…13,14 Because MQ is not commonly used in Benin, the level of resistance to the drug is probably as low as demonstrated by Aubouy in 2005. 15 Similar low levels of resistance have been reported in Nigeria for the period 2007-2008. 16 Assessing the benefit of a drug therapy requires consideration of both therapeutic and adverse effects, which should not be evaluated independently.…”
Section: Discussionsupporting
confidence: 51%
“…13,14 Because MQ is not commonly used in Benin, the level of resistance to the drug is probably as low as demonstrated by Aubouy in 2005. 15 Similar low levels of resistance have been reported in Nigeria for the period 2007-2008. 16 Assessing the benefit of a drug therapy requires consideration of both therapeutic and adverse effects, which should not be evaluated independently.…”
Section: Discussionsupporting
confidence: 51%
“…Despite a possible selection of the women taking only CQ in the study area, these results are consistent with the proportion of MIP evidenced by the pre-trial study (16.7%) and the very high rate of in vivo resistance to CQ (85.7%) found in Ouidah children in 2005. 11 More surprising is the proportion of LBW, slightly higher in the SP-IPTp than in the CQ women, although not significantly. Even if the number of women was small in the CQ group and the selection of these women was probably biased, one cannot rule out the possibility of a direct effect (other than anti-parasitic) of CQ on birth weight, as previously suggested in the pre-trial.…”
Section: Discussionmentioning
confidence: 97%
“…However, the anti-parasite efficacy was not as good as in the trial (11.2% of placenta infection in the delivering women of Tori Bossito versus an overall 2.9% in the trial, 2.1% in the MQ group, and 3.7% in the SP group) in an area where in vivo resistance to SP may reach 50% in children below 5 years. 11 Although populations of women were similar between the clinical trial and the pre-trial study 7 in Ouidah, differences were observed with women from Tori Bossito, although the two sites were only 17 km apart. The latter women were less educated and had a lower attendance to ANVs, which may be characteristic of rural areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SP, previously used as a second-line treatment, was reserved for IPT of pregnant women. Resistance to CQ and SP in vivo was high in Benin previous to this trial (36). The history of drug usage and treatment efficacy is reflected in the parasite genetic diversity in the area.…”
Section: Discussionmentioning
confidence: 99%